To get system B, the second equation in system A was replaced by the sum of that equation and the first equation multiplied by 5. The solution to system B will be the same as the solution to system A.
System A equations:
-x - 2y = 7 ------ (1)
5x - 6y = -3 ------(2)
We multiply the first equation by 5, to get :
-5x - 10y = 35 -----(3)
The sum of equation (2) and equation (3) gives:
-16y = 32
y = 32/-16
y = -2
Thus, solution of system B is;
-x - 2(-2) = 7
-x + 4 = 7
x = -3
So, the solution of system B is (-3, -2), that means the solution of both systems are same.
Read more about equations at; https://brainly.com/question/2972832
#SPJ1